Understanding dance and its non-human agency in Ekman’s “A Swan Lake” - Martina Cayul (Danza e Ricerca)
This article examines Alexander Ekman’s A Swan Lake through new materialisms, focusing on how the introduction of a 6,000-liter lake redefines movement and narrative in ballet. Drawing on Barad’s (2003) concept of intra-action and Bennett’s (2010) notion of thing-power, it explores water as an active agent that transforms the dancers’ techniques and somatic experiences. The first act parodies the legacy of Swan Lake, blending irony with scientific insights into swan behavior. The second act shifts to an immersive exploration of water’s materiality, where its unpredictability creates new choreographic possibilities. By integrating human and non-human materialities, Ekman creates a multisensory experience that challenges traditional representations, offering a posthumanist perspective.